Site-specific function of Endonuclease G and CPS6 to enable vertebrate function in an invertebrate model - Czarny, Ryan Scott, author; Ho, P. Shing, advisor; Stargell, Laurie, committee member; Hansen, Jeffrey, committee member; Argueso, Lucas, committee member (Colorado State University. Libraries, 2021)
The role of mitochondrial localized Endonuclease G (EndoG) remains relatively elusive. Studies have shown that EndoG has implications in mitochondrial DNA copy number, nuclear DNA cleavage during apoptosis, and oncogenesis; however, the mechanisms and pathways have yet to be determined. Our initial work investigates the nuclease activity of EndoG as well as its binding preference for duplex DNA and Holliday Junctions. It appears that EndoG and its C. elegans homolog, cps6, have slightly different functions in their in vivo systems, which has led us to query the structural modifications between the proteins. EndoG has been shown to have a preference for the 5-hydroxymethylcytosine (5hmC) epigenetic marker, an interesting feature due to the fact that invertebrate systems do not contain 5hmC in their epigenome. A key difference in the homologs arises in their DNA binding domain. The invertebrate model (cps6) contains two additional amino acids within this region that potentially allow for an alpha helix not seen in the vertebrate model to form. This alpha helix repositions a conserved cysteine in a way that it is pointed away from the active site in cps6, which could have consequences with regards to function. Our work investigates the addition/removal of this helix from the vertebrate and inveterate system to elucidate its role. In conjunction with the primary DNA binding site, there is a second site next to and orthogonal to the first. The vertebrate system contains multiple positively charged residues positioned to interact with the DNA backbone while the invertebrate contains two prolines that seem to be responsible for repositioning charges away from the site. We investigate the role of this secondary binding site as well as the importance of the invertebrate prolines. Overall, we propose a model to determine the role of EndoG in vivo utilizing the suite of protein mutations characterized herewithin.
Keywords: mitochondria; protein engineering; nuclease; epigenetics